Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA): Stakeholder Engagement Plan (SEP) for Mali cluster activities - Africa Rice Center (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This Stakeholder Engagement Plan (SEP) has been prepared to identify the key stakeholders of the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) Mali Cluster, define information disclosure and stakeholder engagement measures and design a grievance mechanism (GM). The SEP outlines how, when, and ways in which the project team will inform, communicate and consult with stakeholders including vulnerable groups and a mechanism by which people can raise concerns, provide feedback, or make complaints about the project and any activities related to the Project. The SEP has been prepared according to Environmental and Social Standard 10 (ESS 10) on Stakeholder Engagement and Information Disclosure of the World Bank’s Environmental and Social Framework (ESF)and the overall ACCRA SEP prepared by CIAT. It will cover the whole life of the Project. This SEP is a living document and might be updated anytime during project implementation to capture issues that could arise due to the changing circumstances and uncertainties.